A high-resolution seismic investigation for shallow iron ore. Issue 1 (1st December 2019) - Grant, Ashley; Ziramov, Sasha; Urosevic, Milovan
Summary: A high-resolution shallow seismic investigation involving a 3D-3C, 3D-1C, 19 zero-offset ZVSP and a 3D SWD was undertaken in an effort to image a subsurface iron ore deposit. The same project area was used in all of the surveys and was located in north Western Australia. The surveys were acquired over period of 18 months between June 2017 and November 2018. The aim of the investigation was to determine if high-resolution seismic imaging could provide a cost effective means to explore and define shallow high-grade iron ore resource. In this presentation we analyse active source seismic results achieved by two successive 3D seismic surveys. Both sets were calibrated with borehole measurements. The first prominent reflection in the seismic data is at a depth of 15 – 30 m related to the contact at the base of the tertiary detrital sequence. The major iron ore unit is located directly beneath the unconformity and dips gently to the south-west. The grade is variable throughout the survey area and its seismic signature appears to identify some of these changes. Velocity models produced using 3D refraction tomography and surface techniques shows anomalous interval velocities related to the iron rich zone. An elevated amplitude response was also detected in the same zones.